GAMBARAN KEMAMPUAN IBU DALAM PEMBERIAN AWAL MP-ASI DAN RESPON ANAK USIA 6 BULAN DI WILAYAH KERJA PUSKESMAS BENDUNGAN TRENGGALEK - Destiana Prastiwi, Monica; Kasiati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Introduction Proper provision of MP-ASI starts when the child is 6 months old. MP-ASI is given in stages according to the child's age, starting from soft and gentle MP-ASI until the child gets used to family food. The aim of this research is to determine the characteristics of children who are given MP-ASI from an early age, to determine the cognitive abilities of mothers in providing MP-ASI from an early age, to determine the psychomotor abilities of mothers when providing MP-ASI, to determine the physiological condition of children. response after being given MP-ASI. This research design uses exploratory descriptive. Research sample of mothers and babies aged 6 months who provided MP-ASI, incidental sampling technique, questionnaire instruments and observation. The results of the analysis of the mother's ability to initially provide MP-ASI were found to be in the poor category, but over time it became good. The initial response to receiving MP-ASI in children was sufficient, then the child responded by releasing food, the second response was that the children experienced constipation. Analysis Based on the results of research during 4 meetings, there was a gradual increase. The solution in this research is that mothers who have children aged 6 months are given educational information and communication (KIE) in providing correct and appropriate MP-ASI in order to minimize negative responses in children.